Comparative study on molecular epidemiology of measles H1 outbreak and sporadic cases in Shandong Province, 2013–2019 - Suting Wang; Changyin Wang; Xiaodong Liu; Yao Liu; Ping Xiong; Zexin Tao; Meng Chen; Qing Xu; Li Zhang; Aiqiang Xu (BMC Genomics, 2022)
Abstract Background Measles caused by measles virus (MeV) is a highly contagious viral disease which has also been associated with complications including pneumonia, myocarditis, encephalitis, and subacute sclerosing panencephalitis. The current study isolated 33 strains belonging to 2 groups, outbreak and sporadic strains, in 13 cities of Shandong province, China from 2013 to 2019. Comparison of genetic characterization among 15 outbreak strains and 18 sporadic strains was performed by analyzing nucleotide sequences of the C-terminal region of N protein gene (N-450). Results All 33 stains belonged to genotype H1. The outbreak strains and sporadic strains distributed crossly in phylogenetic tree. Sequences alignment revealed some interesting G to A transversion which changed the amino acids on genomic sites 1317, 1422, and 1543. The nucleotide and amino acid similarities among outbreak isolates were 98–100% (0–10 nucleotide variations) and 97.7–100%, respectively; They were 97.3–100% and 96.6–100%, respectively for sporadic isolates. Evolutionary genetics analysis revealed that the mean evolution rates of outbreak and sporadic isolates were 1.26 N 10− 3 and 1.48 N 10− 3 substitutions per site per year separately, which were similar with corresponding data before 2012. Local transmission analysis suggested that there were three transmission chains in this study, two of them originated from Japan. Outbreak cases and sporadic cases emerged alternatively and were reciprocal causation on the transmission chains. Conclusions Our study investigated the phylogeny and evolutional genetics of MeV during a 7-year surveillance, and compared epidemic and genetic characteristics of outbreak strains and sporadic strains. These results underscore the importance of evolutionary study alongside with sporadic cases in discovering and tracing possible outbreaks, especially in the stage of measles elimination.